The Concept of Face of Bilal as the Main Character in the Film Bilal Directed by Ayman Jamal (A Pragmatic Study) - Apriyani, Nanda Hera; Muhammad Anis (Lughaat: Journal of Arabic Linguistics, 2025)
This research is motivated by the fact that Bilal, the animated film, is set around 1,400 years ago. Bilal is the first animated film from the United Arab Emirates, created by 250 animators. This film is based on a true story that showcases the action and adventures of Bilal. It also features highly detailed and imaginative elements. The utterances in the film are formed into face concepts. Therefore, the researcher is interested in examining this film using a pragmatic approach. This study aims to identify and describe positive and negative face concepts in the film Bilal directed by Ayman Jamal. This research employs a descriptive-analytical method by describing the forms of positive and negative faces that appear in the utterances of the main character and analyzing them. Data collection was conducted using observation and note-taking techniques, while the analysis method employed was the extra-lingual matching method. The pragmatic approach was utilized, and the data source was the utterances of the main character Bilal in the film “Bilal”. The analysis results show that the data found in the film includes utterances related to face concepts, specifically positive and negative faces. The positive face data of the main character Bilal often appear in the form of representatives functioning to express or state, used by paying attention to the desires or interests of the interlocutor. Meanwhile, the negative face data of the main character Bilal often appear in the form of representatives functioning to acknowledge, used in a pessimistic manner (self-deprecation).